Construction of nonnilpotent biprimary dispersible groups with metacyclic subgroups of nonprimary index - Zuzuk, L. I. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We give a constructive description of nonnilpotent biprimary dispersible groups with metacyclic subgroups of nonprimary index and classify them into 21 types.